Induced pluripotent stem cells for neural drug discovery. Issue 4 (April 2019) - Farkhondeh, Atena; Li, Rong; Gorshkov, Kirill; Chen, Kevin G.; Might, Matthew; Rodems, Steven; Lo, Donald C.; Zheng, Wei
Highlights: Neural diseases and neuropsychiatric diseases are growing global problems. Effective therapies for neurological diseases are still unmet medical needs. Animal models do not often accurately represent human neurological diseases. Induced pluripotent stem cells are a good model system for human diseases. Abstract : Neurological diseases such as Alzheimer's disease and Parkinson's disease are growing problems, as average life expectancy is increasing globally. Drug discovery for neurological disease remains a major challenge. Poor understanding of disease pathophysiology and incomplete representation of human disease in animal models hinder therapeutic drug development. Recent advances with induced pluripotent stem cells (iPSCs) have enabled modeling of human diseases with patient-derived neural cells. Utilizing iPSC-derived neurons advances compound screening and evaluation of drug efficacy. These cells have the genetic backgrounds of patients that more precisely model disease-specific pathophysiology and phenotypes. Neural cells derived from iPSCs can be produced in a large quantity. Therefore, application of iPSC-derived human neurons is a new direction for neuronal drug discovery.